COMPARATIVE ANALYSIS OF CHANGE IN NEUROPHYSIOLOGICAL AND NEUROCHEMICAL INDICATORS IN TRAINED WORKERS EXPOSED TO MERCURY AND VINYL CHLORIDE - Катаманова, Елена Владимировна; Кудаева, Ирина Валерьевна; Лахман, Олег Леонидович; Рукавишников, Виктор Степанович; Корчуганова, Елена Николаевна; Ещина, Ирина Михайловна (Medicine in Kuzbass, 2020)
Objective. Neurophysiological and neurochemical indicators of trainee workers exposed to mercury and vinyl chloride over time. Purpose – to study the dynamics of changes in neurophysiological and neurochemical parameters in workers exposed to mercury and vinyl chloride. Methods. 131 trainees exposed to mercury and vinyl chloride were examined. All patients underwent clinical neurological examination, electroencephalography, determination of neurochemical parameters of catecholamines, their metabolites and neurotrophic factors in dynamics. Results. In the course of dynamic observation of trainee workers in contact with mercury and vinyl chloride, clinical symptoms worsened with an increase in emotional and personal disorders, an aggravation of cognitive potential and a staged involvement of brain structures in the pathological process according to computer electroencephalography. Under the influence of mercury on neurochemical parameters, its predominant effect on the change in the level of norepinephrine in the dynamics of the examination was established, due, first of all, to the change in its biotransformation into an active metabolite of adrenaline and inactive normetanephrine, an increase in the level of neurotrophic factor CNTF in the dynamics of the examination and a decrease in the levels of NT-3 and BDNF. Under the influence of vinyl chloride, an increase in the levels of adrenaline and norepinephrine, as well as the coefficients of biotransformation of the latter, was noted in dynamics. Field of application: occupational pathology, neurology, toxicology. Conclusion. When exposed to both mercury and vinyl chloride, changes are noted in the dynamics of observation in the field of emotional and cognitive impairments, as well as bioelectric activity of the brain. In addition, the content of catecholamines, primarily norepinephrine, due to the modification of its biotransformation, is more pronounced upon exposure to mercury. Deviations in the content of neurotrophic factors (CNTF, BDNF, and NT-3) are important in the development of disorders and/or compensatory-adaptive reactions only with chronic effects on the body of mercury.